KERENTANAN SOSIAL MASYARAKAT AKIBAT PERGERAKAN SEGMEN SIANOK DI KOTA BUKITTINGGI (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2017)
Bukittinggi City is one of the areas passed by the active faults of Fault Sianok Segment. The movement of this Sianok Segment caused the earthquake regularly in Bukittinggi City area. Many of the consequences caused by the earthquake, including the material loss and causing profound trauma. The research conducted is about the social vulnerability caused by the earthquake disaster due to the movement that occurred in the active segment of Sianok segment in Bukittinggi City. The results showed that the level of vulnerability of the population of each District in Bukittinggi City is High. Of the three sub-districts in Bukittinggi City, the most vulnerable people to earthquake disaster are the elderly and under-five population. In addition, the female population is also more vulnerable to disasters because of the greater number of male population.